2020
DOI: 10.1186/s12884-020-2846-x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and health service predictors of postpartum hemorrhage across 14 district, general and regional hospitals in Thailand

Abstract: Background: Postpartum hemorrhage (PPH) is a preventable complication, however, it remains being the leading cause of maternal mortality and morbidity worldwide including Thailand. Methods: A case-control study to examine the risk factors associated with PPH across the hospitals under the Ministry of Public Health in Thailand, was conducted. A total of 1833 patient birth records and hospital profiles including human and physical resources from 14 hospitals were obtained. A multiple logistic regression was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 36 publications
3
15
0
2
Order By: Relevance
“…This finding of reduced perineal trauma was supported by studies by Gagnon et al (1997) and Hodnett et al (2002) although significance was not reached. In the case control study by Prapawichar et al (2020), hospitals which had below the standard nurse midwife to patient ratio had significantly increased odds of postpartum haemorrhage OR 2.3 (95% CI 1.08 to 4.92, p=0.03). Two studies found that maternal readmission was lower when more midwives or nurses were employed in the organisation (Gerova 2010, Kim 2015).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This finding of reduced perineal trauma was supported by studies by Gagnon et al (1997) and Hodnett et al (2002) although significance was not reached. In the case control study by Prapawichar et al (2020), hospitals which had below the standard nurse midwife to patient ratio had significantly increased odds of postpartum haemorrhage OR 2.3 (95% CI 1.08 to 4.92, p=0.03). Two studies found that maternal readmission was lower when more midwives or nurses were employed in the organisation (Gerova 2010, Kim 2015).…”
Section: Resultsmentioning
confidence: 93%
“…Six studies included only participants at low risk of complications. Three studies included only complex cases such as women having postpartum haemorrhage (Prapawichar et al, 2020), those having oxytocin in labour (Clark et al, 2014) or caesarean section (Kim et al, 2016). The majority of studies (14/21) reported only outcomes relating to labour and birth.…”
Section: Resultsmentioning
confidence: 99%
“…Improper nutrition and lack of enough physical exercise make not only pregnant women themselves gain excessive weight, but also increase the risk of macrosomia in the fetus. An oversized fetus is likely to lead to excessive distension of uterine fibers, thinning of the myometrial wall, and poor myofiber contraction, resulting in PPH [ 14 , 36 ]. During vaginal delivery, macrosomia may prolong the first and second stages of labor and result in severe perineal laceration or even perineal incision.…”
Section: Discussionmentioning
confidence: 99%
“…The overall prevalence of PPH in South-Eastern Asia was previously reported at 4.88% [ 4 ]. In Thailand, the figures varied from 1.4% to 10.6%, depending on the types of health care settings [ 5 ]. The highest prevalence was usually identified in district hospitals where healthcare resources were limited, and the distribution of risk factors was different from hospitals in the urban area [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%